(untitled) (Journal of actual problems of jurisprudence, 2016)
The problem of law definition is considered in the article, it is disclosed scientific approaches to the legal conception in the traditional interpretation, as well as on the bases of the latest legal informational-quantum (cognitiv) paradigm.